Pomiędzy Obrą i Odrą. Tom 2 - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book is divided into historiographic and source parts. The first one includes seven articles about the fate of interesting characters or local but spectacular events. The objects of research interest included the governor of district of Babimost Dobrogost from Kolno, the governor of district of Gniezno Krzysztof Unrug, the owners of Międzychód, Kargowa and Trzciel, Zygmunt and Anna Marianna Kottwitz from Konotop, and the organist from Nowe Kramsko Jan Benyskiewicz. Three articles in this collection concern Kargowa.
Keywords: Babimost (woj. lubuskie); Kargowa (woj. lubuskie); Konotop (woj. lubuskie); Benyskiewicz, Joachim (1936-2011); Unrug, Krzysztof (1624-1689); Dobrogost z Kolna i Prusimia ( -1442/1443); Kottwitz von (ród); Kottwitz, Anna von; Kottwitz, Sigismund von; karczma; mapa; maps